Behavioural Interventions to Reduce Nickel Exposure in a Nickel Processing Plant. - Rumchev, Krassi; Brown, Helen; Wheeler, Amanda; Pereira, Gavin; Spickett, Jeffery (2017)
Nickel is a widely used material in many industries. Although, there is enough evidence that occupational exposure to nickel may cause respiratory illnesses, allergies and even cancer, it is not possible to stop the use of nickel in occupational settings. Nickel exposure, however, can be controlled and reduced significantly in workplaces. The main objective of this study was to assess if educational intervention of hygiene behaviour could reduce nickel exposure among Indonesian nickel smelter workers. Participants were randomly assigned to three intervention groups (n = 99). Group one (n = 35) received only an educational booklet about nickel, related potential health effects and preventive measures, group two (n = 35) attended a presentation in addition to the booklet, and group three (n = 29) received personal feedback on their biomarker results in addition to the booklet and presentations. Pre and post intervention air sampling was conducted to measure concentrations of dust and nickel in air along with worker's blood and urine nickel concentrations. The study did not measure significant differences in particles and nickel concentrations in the air between pre and post interventions. However, we achieved significant reductions in the post intervention urine and blood nickel concentrations which can be attributed to changes in personal hygiene behaviour. The median urinary nickel concentration in the pre-intervention period for group one was 52.3 µg/l, for group two 57.4 µg/l and group three 43.2 µg/l which were significantly higher (p< = 0.010) than those measured in the post-intervention period for each of the groups with 8.5 µg/l, 9.6 µg/l and 8.2 µg/l, respectively. A similar pattern was recorded for serum nickel with significantly (p <0.05) higher median concentrations measured in the pre-intervention period for group one 1.7 µg/l, and 2.0 µg/l for group 2 and group 3 compared with the post intervention median serum nickel levels of 0.1 µg/l for all groups. The study showed that educational interventions can significantly reduce personal exposure levels to nickel among Indonesian nickel smelter workers.